Penerapan Cognitive Behavioral Therapy Untuk Meningkatkan Self-Identity Generasi Z Siswa Kelas VIII A di SMP Negeri 3 Denpasar - I Gusti Lanang Rai Arsana; Made Wery Dartiningsih; Ziadatun Nufus; Hestika Angelina Rukka (Universitas Muria Kudus, 2024)
This study aims to examine the implementation of Cognitive Behavioral Therapy (CBT) to enhance self-identity among Generation Z students in class VIII A at SMPN 3 Denpasar. The research employed a quantitative approach with a pre-experimental design, specifically using the one-group pre-test post-test design. The subjects of the study consisted of 8 students from a single class. Data was collected through pre- and post-intervention questionnaires assessing self-identity. The results indicated a significant improvement in self-identity scores following the CBT intervention, with students showing increased self-awareness, self-acceptance, and a clearer sense of personal values. The findings suggest that CBT can be an effective method for enhancing self-identity in adolescents, particularly in the context of Generation Z students.